COMPLIANCE TO COLONOSCOPY IN PATIENTS VISITING THE DEPARTMENT OF GASTROENTEROLOGY AT LADY READING HOSPITAL, PESHAWAR - Durrani, Talha; Humayun, Omama; Khan, Osama Sherjeel; Qazalbash, Zeeshan Ali; Durrani, Daniyal; Imran Ullah, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Colorectal cancer is the largest cause of mortality in patients admitted to any Gastroenterology units. Diagnostic colonoscopy is a valuable tool for the disease's diagnosis and proper treatment but its compliance has been historically low. Our main objective was to find out social, cultural, and psychological barriers among those patients who finally did not show up for their colonoscopy appointment and, make a comparative analysis with those who did. Methods: A cross-sectional study was conducted in the Lady Reading Hospital, Peshawar from October 2021 to March 2022, selecting 224 patients through consecutive sampling. Results: Out of the 224 patients included, males (48.2%) were more likely to show up for the procedure than females (51.8%) (p<0.05). Overall, the most recurring barrier was a lack of knowledge with 116 (51.7%) for both the groups, but especially more for the non-compliant patients (p<0.05). Fear of results, fear of complications of the procedure, and affordability issues stood out as important differences between the compliant and non-compliant patients. Conclusion: For the country's healthcare to be able to overcome these problems, and enter an era where screening colonoscopy is a norm, mass education regarding the issue is imperative.